2016
DOI: 10.1002/pen.24384
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenes in blown films: Effect of molecular structure on sealability and crystallization kinetics

Abstract: Three types of polyethylene (PE), with different molecular structure, were selected and used in the production of films using a semi‐industrial blown film extrusion line. Carbon nuclear magnetic resonance and crystallization analysis fractionation tests were performed on the PE polymers to assess their molecular structure. Sealability properties of the films, as well as crystallization kinetics, were evaluated and the results are discussed according to the molecular structures of the polymers. It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In general, the actual distribution of short chain branches influences the beginning of sealability, or Sealing Initiation Temperature (SIT). A perfectly random inclusion of branches causes indeed the formation of smaller lamellae in blown films, as also suggested by lower melting temperature of the films in the first heating scan of DSC . This may seem to provide a target for the polymer design to obtain low SIT, however low melting temperature is undesirable as it makes processing more difficult.…”
Section: Polymer‐based Crystallinity Modificationsmentioning
confidence: 80%
“…In general, the actual distribution of short chain branches influences the beginning of sealability, or Sealing Initiation Temperature (SIT). A perfectly random inclusion of branches causes indeed the formation of smaller lamellae in blown films, as also suggested by lower melting temperature of the films in the first heating scan of DSC . This may seem to provide a target for the polymer design to obtain low SIT, however low melting temperature is undesirable as it makes processing more difficult.…”
Section: Polymer‐based Crystallinity Modificationsmentioning
confidence: 80%
“…However, when the polymer shows a slower crystallization behavior or when the applied seal temperatures are much higher than the crystallization temperature, the hot tack seal strength will be more related to the interdiffusion rate than the solidification. 53 Also according to the study of Simanke et al, between two metallocene linear LLDPE fractions, it can be observed that the sample having a higher crystallization temperature shows better hot tack performance than the other one. This feature can be attributed to the immediate recrystallization of the m-LLDPE molecules after the sealing process, because of its higher crystallization temperature.…”
Section: Seal Bar Designmentioning
confidence: 96%
“…In the case of semicrystalline polymers like polyethylene, the sealing temperature must be near the melting temperature of the matrix polymer to allow sufficient mobility of polymer chains across the interface. The seal strength, failure mode, and appearance of these seals after cooling to room temperature are important parameters for end use applications 15–19 . It has been established that the crystallinity of polyolefins and ethylene copolymers affected the seal strength 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that the crystallinity of polyolefins and ethylene copolymers affected the seal strength 16 . Furthermore, the heat seal strength depends on the extent of molecular penetration, that is, intermolecular diffusion, across the melt interface during the sealing process 15,19 . Thus, sealing behavior of the LLDPE/LDPE would be depending on the intermolecular diffusion of the LLDPE and LDPE polymer chains during sealing process.…”
Section: Introductionmentioning
confidence: 99%